Estimasi Cadangan Karbon Dan Serapan Karbon Di Taman Maluku Kota Bandung - Ina Darlina; Sri Wilujeng; Fajar Nurmajid (Paspalum: Jurnal Ilmiah Pertanian, 2023)
The availability of green open space (RTH) in urban areas is very important to mitigate the effects of global warming, especially in reducing CO2 gas levels as a result of human activities. Vegetation with chlorophyll, namely the trees in green open spaces try to absorb carbon dioxide (CO2) using sunlight, water and soil from the atmosphere through the process of photosynthesis. One form of stored photosynthetic results is biomass which makes this vegetation grow bigger and taller . In the carbon cycle and biogeochemical cycle the biomass of green open space vegetation plays an important role, all parts starting from the stems, leaves and roots store biomass. This study aims to determine the estimation of carbon stocks and absorption in Taman Maluku, Bandung City. The method used in this study is a non-destructive method (without harvesting). The research was conducted by collecting tree data and the wet weight of the understorey, then calculating the biomass to obtain estimates of carbon stocks and carbon absorption. From the research it was found that the Maluku Park in Bandung City with an area of 23,633 m2 has carbon reserves of around 179.941 tons from trees and 3.11 tons from undergrowth. Meanwhile, the estimated carbon uptake is 731,422 tonnes by trees and 11,409 tonnes by undergrowth. The high carbon stock can be influenced by several factors including: vegetation density, environment, especially sunlight, volume, specific gravity, wood constituents, water content, and silvicultural measures.